Neoadjuvant therapy alters the immune microenvironment in pancreatic cancer - Zhang, Huiru; Ye, Longyun; Yu, Xianjun; Jin, Kaizhou; Wu, Weiding (Frontiers in Immunology, 2022)
Pancreatic cancer has an exclusive inhibitory tumor microenvironment characterized by a dense mechanical barrier, the profound infiltration of immunosuppressive cells and a lack of penetration of effector T cells, which constitutes an important cause for recurrence and metastasis, resistance to chemotherapy and insensitivity to immunotherapy. Neoadjuvant therapy has been widely used in clinical practice due to its many benefits, including the ability to improve the R0 resection rate, eliminate tumor cell micrometastases and identify highly malignant tumors that may not benefit from surgery. In this review, we summarize multiple aspects of the effect of neoadjuvant therapy on the immune microenvironment of pancreatic cancer, discuss possible mechanisms by which these changes occur and generalize the theoretical basis of neoadjuvant chemoradiotherapy combined with immunotherapy, providing support for the development of more effective combination therapeutic strategies to induce potent immune responses to tumors.